Wages and Mobility: The Impact of Employer‐Provided Training - Parent, Daniel (Journal of Labor Economics, 1999)
Using data from the National Longitudinal Survey of Youth, this article examines the impact of employer‐provided training on the wage profile and on the mobility of young workers. The main results are that (i) training with the current employer has a positive effect on the wage; (ii) employers seem to reward skills acquired through training with previous employers as much as skills they provide themselves; and (iii) part of the skills acquired through training programs provided by the current employer seem to be fairly specific as they are shown to reduce mobility, even after controlling for unobserved heterogeneity.